KAJIAN AWAL KEDUDUKAN OMNIBUS LAW DALAM PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Muhammad Rusydi DR; Muhtar Said (Universitas Trisakti, 2024)
As a state of law, Indonesia, which adheres to the Civil Law system, actually makes omnibus law which is a legal system of Common Law. The omnibus law is considered to be the answer to the overlapping of all existing laws and regulations in Indonesia. Omnibus Law if it is associated with the Legal System in Indonesia is contrary to the system that has been applied in Indonesia. There are 7 factions that agree and 2 factions that reject the discussion of the Omnibus Law Bill. In the process, Article 5 of Law No. 12 of 2011 and Law No. 15 of 2019 contains the principle of the formation of legislation, one of the problems in the formation of the Omnibus Law Bill is the principle of openness. This is because there are various indications, including the exclusion of groups related to or having an impact on this Omnibus Law Bill. There was also a member of the DPR who was supposed to be one of the working committees (Panja) to discuss the Omnibus Law Bill which was not involved because there was no notification. There is also a difference in the number of pages in the Omnibus Law Bill. In the regulations, referring to Law Number 12 of 2011 and Law Number 15 of 2019 concerning changes to the Formation of Laws, there are no clear norms and explanations regarding the Omnibus law process both in forming laws and revising laws. The absence of a legal basis for the formation of this omnibus law rules out the legitimacy of a law. Thus the position of Omnibus Law in Indonesia is not in accordance with the existing legal system in Indonesia, especially related to the Indonesian legal system (Civil Law) and Law Number 12 of 2011 and Law Number 15 of 2019 concerning Amendments to Law Number 12 of 2011 concerning the Establishment of Legislation.